Rancang Bangun Sistem Presensi Website Berbasis GPS Di PT Cempaka Mega Mandiri - Steven Jonathan Roy; Prya Artha Widjaja (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
PT Cempaka Mega Mandiri is a company engaged in processing and selling swallow's nests, both for export and in the local market. Currently, it is known that the attendance system used in this company has an unsatisfactory level of accuracy. Therefore, the author decided to apply GPS technology to increase efficiency in the attendance process, in the hope of providing a better solution for the company. GPS, which stands for Global Positioning System, is a navigation system that uses satellites to identify and synchronize location data from an object on the earth's surface. In this context, the application of GPS technology is considered a strategic step to increase the accuracy of recording employee attendance. This research uses the SDLC Waterfall method as a software development approach. This method involves sequential stages, starting from planning, analysis, design, implementation, testing, to maintenance. The result of this research is the development of a GPS-based attendance website, which is expected to provide an effective solution for improving the attendance system at PT Cempaka Mega Mandiri.